Which factors are helpful for the early determination of treatment level in patients with interstitial lung disease in the intensive care unit to minimize the suffering in their end of life?: A retrospective study. Issue 37 (16th September 2022) - Kim, Sun-Hyung; Lee, Dong-Hwa; Yang, Bumhee; Cho, Jun Yeun; Kang, Hyeran; Choe, Kang Hyeon; Lee, Ki Man; Shin, Yoon Mi
Abstract : Interstitial lung disease (ILD) is widely known to be associated with high mortality and poor prognosis, especially in patients admitted to the intensive care unit (ICU). The objective of this study was to investigate clinical predictors for assisting relatively early decision of treatment level in the ICU. We retrospectively investigated patients with ILD who were admitted to the ICU between January 1, 2014, and September 30, 2019. A total of 64 patients were analyzed. We found the ICU and hospital mortality rates to be 67.2% and 69.8%, respectively. Nonsurvivors had a higher fraction of inspired oxygen (FiO2 ) on days 1 (79 ± 21 vs 60% ± 21%, P = .001) and 3 (61 ± 31 vs 46% ± 19%, P = .004). They showed lower partial pressure of oxygen/FiO2 (PF) ratio on days 1 (134 ± 80 vs 173 ± 102, P = .049) and 3 (147 ± 74 vs 235 ± 124, P = .003) than the survivor group. The lactic acid levels obtained on day 1 and PF ratio measured on day 3 were associated with mortality (odds ratio, 1.89; 95% confidence interval 1.03–3.47 and odds ratio, 0.99; 95% confidence interval 0.98–1.00, respectively). Among the 31 ICU survivors, 10 patients died in the general ward, 12 patients died after hospital discharge; only 9 patients survived after 1 year. We suggest that these clinical predictors could be used to determine the level of further treatment or withdrawal on day 3 of admission in patients with ILD admitted to the ICU to minimize the prolonged suffering in a relatively early period.